Semangat Undang-Undang Nomor 25 Tahun 2009 Versus Mentalitas Birokrat (Tinjauan Kritis Konten Undang-Undang Pelayanan Publik) - Mita Widyastuti (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2012)
The quality of bureaucracy service has been complained by most society, starting from the matter of fare, procedure, officer's response, discriminative service, until abusive attitude. Whereas society expectation emerges along the bureaucracy reformation since 1998 with drastic change in the field of the regulation of local government implementation which is more decentralized. One of the forms is to stipulate the legislation number 25 year 2009 about Public Service. Explicitly, there is an admission of public rights in gaining public service, including inside is the increase of public service quality. There has been paradigm shift in public service, from the old public administration model to the new public management, and finally to new public service (Denhardt and Denhardt, 2000). The latest model is new public management, it views the service implementation can be diversification the service based on customer characteristic. Customer who has higher economic skill can choose better service with different fare. Thus, society does not have the same right in obtaining public service. One of the strategies to increase the quality of public service is to seek best-practice, then it becomes the guideline, and is stated as an obligation for all employee so that they obtain motivation to do the same thing with the host best practice.